2010
DOI: 10.1002/tea.20381
|View full text |Cite
|
Sign up to set email alerts
|

Resisting the marginalization of science in an urban school: Coactivating social, cultural, material, and strategic resources

Abstract: This study describes the resources and strategies middle school teachers, urban fellows, and a district science staff developer coactivated to resist the marginalization of science in a high‐poverty, low‐performing urban school. Through critical narrative inquiry, I document factors that marginalized science in three teachers' classrooms. The narratives show that constraints related to cultural, material, and social resources contributed to a more global symbolic resource constraint, the low status and priorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 38 publications
3
34
0
1
Order By: Relevance
“…As evident in the research above, scholars should continue to examine how teachers navigate through the challenges of low student achievement (in terms of standardized tests), limited resources, and pervasive deficit models. All of these factors are results of students being continuously marginalized not only in science, but school and society (Otsuki, 2009;Patchen & Cox-Petersen, 2008;Rivera Maulucci, 2010). This line of inquiry requires us to consider a wide range of voices from students who do not fit the typical profile of American teachers: White, female, and middle-class.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As evident in the research above, scholars should continue to examine how teachers navigate through the challenges of low student achievement (in terms of standardized tests), limited resources, and pervasive deficit models. All of these factors are results of students being continuously marginalized not only in science, but school and society (Otsuki, 2009;Patchen & Cox-Petersen, 2008;Rivera Maulucci, 2010). This line of inquiry requires us to consider a wide range of voices from students who do not fit the typical profile of American teachers: White, female, and middle-class.…”
Section: Resultsmentioning
confidence: 99%
“…The teacher was accustomed to FOSS kits (an interactive/hands-on science kit) and was forced to give her students instruction using the more traditional note-taking style. Maulucci (2010) found that limited resources could further marginalize the students in the study if teachers felt helpless in supplying their students with the distinct resources their population needed. However, in this study, teachers adapted and learned how to use their social, symbolic, and strategic resources, in lieu of economic resources (i.e.…”
Section: Limited Resourcesmentioning
confidence: 99%
“…Una de las estrategias educativas que mayor impacto ha generado en la superación de la pobreza es que los niños y las niñas menores de seis años tengan la oportunidad de acceder a recursos y programas de desarrollo cognitivo y socioemocional. Además, el establecimiento de un currículo de máximos, especialmente en las áreas instrumentales (Maulucci, 2010;Hammond, 2001) o la extensión del tiempo de aprendizaje (Arnold & Doctoroff, 2003;Mahoney, Lord & Carryl, 2005;Taylor, Power & Rees, 2010) son factores esenciales para el éxito académico y el acceso a la educación post-obligatoria (Baum & Flores, 2011) de las personas que viven en contextos empobrecidos.…”
Section: La Lucha Contra La Pobreza a Través De La Educaciónunclassified
“…Morrison, Robbins, and Rose () conducted a meta‐analysis of research on the implementation of CRP and suggested CRP “ultimately clashes with the traditional ways in which education is carried out in society” (p. 444), and this may be the reason teachers are unable to change their practice. As with other significant instructional paradigm shifts, teachers adopting CRP will need professional development support to make the transition to the constructivist mode of teaching that CRP requires (Johnson, ; Lee, Penfield, & Maerten‐Rivera, ; Morrison et al., ; Rivera Maulucci, ).…”
Section: Teacher Beliefs Regarding Diversity and Culturementioning
confidence: 99%